Pengaruh Citra Merek Dan Promosi Terhadap Loyalitas Pelanggan: (Survei Pada Pelanggan Insan Sport Di Tasikmalaya) - Euis Dewi Mustika Bella (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
This study aims to determine the simultaneous and partial effect of brand image and promotion on customer loyalty of Insan Sport in Tasikmalaya. The method used in this research is a survey method with a quantitative approach. The population studied was 100 respondents. The data collected in the form of primary data and secondary data. Analysis of the data in this study using multiple linear regression analysis using SPSS veris 24 software. The results showed that brand image and promotion simultaneously had a significant effect on customer loyalty in Insan Sport in Tasikmalaya. Brand Image, partially has a significant effect on customer loyalty of Insan Sport in Tasikmalaya. Promotion partially has a significant effect on customer loyalty of Insan Sport in Tasikmalaya.